2003
DOI: 10.1080/02841850312331287799
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative assessment of left ventricular volume with ECG-gated multislice spiral CT: value of different image reconstruction algorithms in comparison to MRI

Abstract: Multisegmental image reconstruction improves the quantitative assessment of left ventricular function when compared to standard image reconstruction. Multisegmental image reconstruction allows qualitative wall motion analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…A lesser amount of information on regional wall motion evaluation with CT has been reported [9, 28,31,32,33,34,35,36,37]. In our study, areas of impaired motion identified by CT showed good agreements in comparison with LVG and CMR in segmental analysis.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…A lesser amount of information on regional wall motion evaluation with CT has been reported [9, 28,31,32,33,34,35,36,37]. In our study, areas of impaired motion identified by CT showed good agreements in comparison with LVG and CMR in segmental analysis.…”
Section: Discussionsupporting
confidence: 63%
“…The feasibility of CT for the evaluation of LV function has been investigated [9, 10,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. LV functional analysis by CT has its inherited disadvantage including a higher radiation dose (by avoiding dose modulation protocols) and a longer postprocessing time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, analysis of multiplanar reformations of retrospectively ECG-gated MDCT coronary angiography data permits the assessment of left ventricular function and volumes [18]. However, the major drawback of MDCT measurements is the overestimation of EDV and ESV compared with MRI as the standard of reference.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the ability of electronbeam computed tomography and multidetector spiral computed tomography (MDCT) to assess left ventricular function and mass by multiplanar reformation algorithms using short-axis images (9,13,18,19). Due to retrospective gating used for cardiac MDCT, all data for the analysis of left ventricular parameters can be calculated from a standard MDCT coronary angiography data set without any additional radiation exposure.…”
mentioning
confidence: 99%